Learning and belonging: Decolonial and Indigenous approaches to gender diversity in higher education (Journal of Applied Learning and Teaching, 2026)
This article examines the role of intercultural education in creating higher education spaces that affirm and recognise the social identities of transgender and gender-diverse individuals, focusing on Global South and Indigenous perspectives. It explores how Western-centric cisnormative frameworks inform institutional policies and pedagogical practices, often marginalising these identities. Moreover, while there has been a growing awareness of transgender issues, this discourse is predominantly shaped by Global North perspectives, which overlook the diverse ways of knowing and experiencing gender. Through a decolonial lens, the paper introduces the Intercultural Triadic Framework, which integrates Indigenous epistemes, gender diversity, and pedagogical transformation to guide more plural approaches to teaching and learning. Drawing on a qualitative case study of an intercultural competence course at King’s College London, it demonstrates how theory can move into praxis through reflective activities and collaborative learning. For many transgender and gender-diverse individuals, school can be a site of violence, emphasising the pressing need for institutional change. Education should allow spaces for learning but also for affirming humanity. To this end, it emphasises the importance of engaging activists, students, and educators who identify as transgender or gender-diverse in co-creating intercultural competency. This study contributes to ongoing dialogues about inclusion in higher education by amplifying the perspectives of Indigenous and Global South transgender and gender-diverse individuals. It highlights the importance of intercultural competencies in instilling empathy and understanding within educational spaces. Ultimately, it is about creating opportunities for all individuals to thrive and have a sense of belonging.